In-vitro evaluation of the immunomodulatory effects of Baricitinib: Implication for COVID-19 therapy. Issue 4 (April 2021) - Petrone, Linda; Petruccioli, Elisa; Alonzi, Tonino; Vanini, Valentina; Cuzzi, Gilda; Najafi Fard, Saeid; Castilletti, Concetta; Palmieri, Fabrizio; Gualano, Gina; Vittozzi, Pietro; Nicastri, Emanuele; Lepore, Luciana; et al.
Highlights: Baricitinib has been suggested as a promising therapy for COVID-19. Baricitinib modulates in vitro SARS-CoV-2-specific-response in a whole blood platform. Baricitinib decreases viral-specific-response mainly in mild/moderate COVID-19. Abstract: Objective: Baricitinib seems a promising therapy for COVID-19. To fully-investigate its effects, we in-vitro evaluated the impact of baricitinib on the SARS-CoV-2-specific-response using the whole-blood platform. Methods: We evaluated baricitinib effect on the IFN-γ-release and on a panel of soluble factors by multiplex-technology after stimulating whole-blood from 39 COVID-19 patients with SARS-CoV-2 antigens. Staphylococcal Enterotoxin B (SEB) antigen was used as a positive control. Results: In-vitro exogenous addition of baricitinib significantly decreased IFN-γ response to spike- (median: 0.21, IQR: 0.01–1; spike+baricitinib 1000 nM median: 0.05, IQR: 0–0.18; p  < 0.0001) and to the remainder-antigens (median: 0.08 IQR: 0–0.55; remainder-antigens+baricitinib 1000 nM median: 0.03, IQR: 0–0.14; p  = 0.0013). Moreover, baricitinib significantly decreased SEB-induced response (median: 12.52, IQR: 9.7–15.2; SEB+baricitinib 1000 nM median: 8, IQR: 1.44–12.16; p  < 0.0001). Baricitinib did modulate other soluble factors besides IFN-γ, significantly decreasing the spike-specific-response mediated by IL-17, IL-1β, IL-6, TNF-α, IL-4, IL-13, IL-1ra, IL-10, GM-CSF, FGF, IP-10, MCP-1, MIP-1β ( p  ≤ 0.0156). The baricitinib-decreased SARS-CoV-2-specific-response was observed mainly in mild/moderate COVID-19 and in those with lymphocyte count ≥1 × 10 3 /µl. Conclusions: Exogenous addition of baricitinib decreases the in-vitro SARS-CoV-2-specific response in COVID-19 patients using a whole-blood platform. These results are the first to show the effects of this therapy on the immune-specific viral response. Graphical abstract: Image, graphical abstract